Evaluation of antibacterial effects of contemporary orthodontic bonding materials - Baka, Zeliha Muge; Eldeniz, Ayce Unverdi; Guneser, MEHMET BURAK; GÜNEŞER, MEHMET BURAK; Basciftci, Faruk Ayhan (My University, 2017)
Aim: The aim of this study was to evaluate the antibacterial effects of five orthodontic bonding materials commonly used in orthodontics. Materials and Methods: The antibacterial effects of five orthodontic bonding materials were evaluated against Streptococcus mutans and Streptococcus salivarius by direct contact test (DCT). Using the DCT technique, quintet specimens of Transbond XT, Blugloo, Grengloo, Light Bond, and Opal Bond were applied to the bottom and the walls of the five wells of a 96-microtiter plate with a height of 2 mm. Samples were prepared in two sets: 1-day samples and 7-day samples. Ten microliters of bacterial suspension were added to each well for direct contact with each material for 1h at 37 degrees C. Bacterial growth was then measured in a microplate spectrophotometer hourly at 600 nm for 24h. Five uncoated wells with identical inoculum sizes served as positive controls. The data obtained at the end of 24h was statistically analyzed with one-way ANOVA, and post hoc comparisons were done using Tamhane-s T2 test. Results: Blugloo generally showed better antibacterial activity than the other materials. Transbond XT did not show any antibacterial activity. There was a statistically significant difference between Transbond XT and Light Bond in the 1-day sample against S. mutans (p0.05). Conclusion: Blugloo had the most potent antibacterial activity against S. salivarious.